Effects of Abelmoschus Esculentus Infused Water on Blood Glucose Levels of Rattus Norvegicus in Hyperglycemia Conditions - Siti Zaenab (IKIP Mataram, 2024)
Efforts to find alternative medicines or herbal-based interventions for diabetes sufferers are very necessary. The aimed of this study was to find out whether the use of okra fruit infusion (Abelmoschus esculentus) with different administration frequencies can reduce the blood sugar levels of hyperglycemic white rats (Rattus norvegicus), and to find out what frequency of giving okra fruit infusion can reduce blood sugar levels. white rat (Rattus norvegicus) tallest. This type of research is true experimental, consisting of 5 treatment groups, (P0-, P0+, P1, P2, and P3), namely negative control, positive control, giving 6 ml of okra fruit infusion water/day given once, giving infused water 6 ml of okra fruit/day was given 2 times a day and 6 ml of okra fruit infusion water was given 3 times a day. Each group consists of 5 repetitions. The research was carried out at the Chemistry Laboratory, Muhammadiyah University of Malang. The data collection method was by measuring the blood glucose levels of white mice that had been treated, then analyzing them using SPSS. Based on the results of data analysis and discussion, it can be concluded that there is an effect of the frequency of administration of okra fruit infusion on reducing blood sugar levels in white rats (hyperglycemia. Treatment P3 is a group of hyperglycemic rats that were given okra fruit infusion water at a dose of 6 ml/head/day, given once a day in the morning and P2, namely the group of hyperglycemic mice that were given okra fruit-infused water at a dose of 6 ml/head/day, given 2x a day in the morning and evening, is the best treatment because it has the same notation as P0 (negative control) or the group of mice that not given water infused with okra fruit and not given alloxan. Giving an infusion of okra fruit at a dose of 6 ml/head given once in the morning or twice (morning and evening) has an effect on reducing the blood sugar levels of hyperglycemic white mice. Okra can be consumed fresh, processed by boiling, or frying, dry, but not made into flour.